Analysis and correlation of ultraviolet solar radiation from routine meteorological measurements over Egypt - SALEM, A. I. (MAUSAM, 2000)
For three years (1990-92) measurements of the monthly average daily global, G, and ultraviolet, UV, solar radiation incident on a horizontal surface at Cairo (30°15'N, 31°17'E) and Aswan (23°58'N, 32°47'E) are presented. processed and analysed. It was found that the computed monthly average daily values for the obtained solar radiation components, G and UV, were (18.1 MJ/m2, 0.55 MJ/m2, for Cairo and (22.1 MJ/m2, 0.71 MJ/m2, for Aswan. The effect of atmospheric dust on the measured solar radiation components is also investigated and discussed. The ratio of the ultraviolet to global radiation (UV/G) are calculated and compared with other sites in the Arabian Peninsula. A regression analysis has been done to find a correlation between G and UV at the selected sites during the three year period and the recommended correlation equations have also been stated. Since the meteorological measurements of UV solar radiation are not available over Egypt. except at Cairo (Lower Egypt) and Aswan (Upper Egypt) stations, our correlation equations can be used to calculate this component from the available global solar radiation measurements at any site in the two zones of Upper and Lower Egypt.